Penilaian pengolahan limbah cair industri farmasi PT. Nusantara Beta Farma Padang dan pengaruhnya terhadap lingkungan - Sri Nanda Ayusa; Bintal Amin; Dedi Afandi (Pelantar Press, 2018)
Pharmaceutical industry PT . Nusantara Beta produce drugs - drugs and drug classes classes Free Free Limited . Thus the need for a treatment for a review dispose of waste Which has a raw quality that corresponds to the applicable government regulations . Already QUALITY liquid waste is processed through the WWTP already meet the Liquid Waste Quality in accordance with Minister of Environment 51 / MENLH / 10/1995 . From the findings of the WWTP ON ANOVA test concentration of TSS and phenol NOT show the real difference between Station , ON parameter while the COD , BOD5 and Total N has the real difference between AT Namely Station Station 1 has the distinction Yang Against Station 2 and Station 3. QUALITY Parameter waters river TSS , total N and pH are in accordance with the raw water quality Government Regulation No. 82 of 2001 , based on aNOVA test stations are ON EACH waters show There are real differences between the stations.